1992
DOI: 10.1111/j.1532-5415.1992.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss Prevalence and Management in Nursing Home Residents

Abstract: Residents should have hearing evaluations with documentation of results on admission and periodically under the direction of a nurse trained as a hearing specialist. Environmental modifications of the NH plus use of hearing aids can improve hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…In a study focusing on nursing home residents, Garahan et al (1992) reported that the prevalence of moderate to severe hearing loss was 51 percent, while another study reported that 22 percent of nursing home residents had moderate to severe hearing loss (Voeks et al, 1990). Differences in measurement and classification of hearing impairment may partly explain the dissimilar findings.…”
mentioning
confidence: 87%
“…In a study focusing on nursing home residents, Garahan et al (1992) reported that the prevalence of moderate to severe hearing loss was 51 percent, while another study reported that 22 percent of nursing home residents had moderate to severe hearing loss (Voeks et al, 1990). Differences in measurement and classification of hearing impairment may partly explain the dissimilar findings.…”
mentioning
confidence: 87%
“…14 Cerumen impaction is more common in the elderly and in patients with cognitive impairment. Estimates suggest that between 19% and 65% of patients >65 years old have cerumen impaction 13,15 and that elderly patients in nursing homes are likely at the upper end of this spectrum. 10,18 In the developmentally delayed adult population, 28% to 36% have excessive or impacted cerumen.…”
Section: Health Care Burdenmentioning
confidence: 99%
“…3,10,11 About 12 million people in the United States annually seek medical care for problematic cerumen, resulting in nearly 8 million cerumen removal procedures. 12,13 Nearly $50 million was spent by Medicare in 2012 for cerumen-related procedures, and cerumen impaction was a diagnosis in up to 5% of Medicare patients. 14 Moreover, excessive or impacted cerumen in high-risk populations, such as the elderly and developmentally delayed, is underdiagnosed and likely undertreated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,10 About 12 million people seek medical care annually for problematic cerumen in the United States, resulting in nearly 8 million cerumen removal procedures. 11,12 Nearly $50 million was spent by Medicare in 2012 for cerumen-related procedures, and cerumen impaction was a diagnosis in up to 5% of Medicare patients. 13 Moreover, excessive or impacted cerumen in high-risk populations, such as the elderly and developmentally delayed, is underdiagnosed and likely undertreated.…”
Section: Introductionmentioning
confidence: 99%